The effects of feeding different levels of dicalcium phosphate to heifers on bluestem pasture - Drake, C.L.; Smith, E.F.; Richardson, D.; Good, D.L.; Follis, D.L. (Kansas Agricultural Experiment Station, 2011)
This trial was designed to study the effects of low to high levels of calcium and phosphorus supplementation for heifers grazing bluestem pasture. Forty Hereford heifer calves were divided into four groups at random, and turned into a 140-acre pasture. Each morning the heifers were gathered and separated into four lots and fed the rations shown in Table 14.
Keywords: Beef; Dicalcium phosphate; Heifers; Bluestem pasture